Nautilus - Keane, David, 1943-2017 (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1988)
Nautilus was commissioned by Newfoundland clarinetist Paul Bendzsa (with the assistance of a Canada Council Commissioning Grant). The work will have its premiere performance in July at the Sound Symposium, a biennial festival that takes place in St. John's, Newfoundland. This performance in Bourges substitutes a synthesized clarinet for the live soloist. The nautilus is a sea mollusk that erects an impressive chambered shell. The music makes the analogy of the clarinet as the living creature and the electronic sound as the shell which grows ever larger and increasingly beautiful. At first the solo and accompaniment are relatively indistinguishable from one another, but in time they become quite separate and in the end only the inert shell remains. Nautilus was realized in the composer's personal studio in Toronto.